Application of continuous positive airway pressure in the delivery room: a multicenter randomized clinical trial - Gonçalves-Ferri,W.A. (2014)
This study evaluated whether the use of continuous positive airway pressure (CPAP) in the delivery room alters the need for mechanical ventilation and surfactant during the first 5 days of life and modifies the incidence of respiratory morbidity and mortality during the hospital stay. The study was a multicenter randomized clinical trial conducted in five public university hospitals in Brazil, from June 2008 to December 2009. Participants were 197 infants with birth weight of 1000-1500 g and without major birth defects. They were treated according to the guidelines of the American Academy of Pediatrics (APP). Infants not intubated or extubated less than 15 min after birth were randomized for two treatments, routine or CPAP, and were followed until hospital discharge. The routine (n=99) and CPAP (n=98) infants studied presented no statistically significant differences regarding birth characteristics, complications during the prenatal period, the need for mechanical ventilation during the first 5 days of life (19.2 vs 23.4%, P=0.50), use of surfactant (18.2 vs 17.3% P=0.92), or respiratory morbidity and mortality until discharge. The CPAP group required a greater number of doses of surfactant (1.5 vs 1.0, P=0.02). When CPAP was applied to the routine group, it was installed within a median time of 30 min. We found that CPAP applied less than 15 min after birth was not able to reduce the need for ventilator support and was associated with a higher number of doses of surfactant when compared to CPAP applied as clinically indicated within a median time of 30 min.